PERBEDAAN HASIL PEMERIKSAAN HEMATOLOGI BERDASARKAN DERAJAT KEPARAHAN PASIEN COVID-19 DI RUMAH SAKIT SEMEN PADANG TAHUN 2021 - Puja, Annisa Fitria; Efrida, Efrida; Permana, Hendra; Yulia, Dwi; Welan, Rahmani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Objective: To determine differences in the results of hematological examinations based on the severity of COVID-19 patients at Semen Padang Hospital in 2021. Methods: The type of research was observational analytic with a cross-sectional design. We took secondary data from the medical records of COVID-19 patients. A total of 100 patients were included in this study was conducted at Semen Padang Hospital in January-December 2021. Bivariate analysis used a one-way ANOVA with the Kruskal-Wallis alternative. The results are considered as significant if p <0.05. The significance of the parameters was tested using the Post Hoc Scheffe (p<0.05). Results: From 100 patients found the: 60% Male and 40% female, mean age of 51.95 ± 12.82 years, mild COVID-19 patients 36%, moderate 44%, severe 14%, and critical 6%. The mean hematological parameters were within normal limits. Hemoglobin levels (g/dL) of male patients based on severity (mild, moderate, severe, and critical) were 15,02 ± 1,10, 14,20 ± 1,29, 14,14 ± 1,21, 14,50 ± 1,99 respectively (p<0.05); hemoglobin levels (g/dL) of female patients were 13,73 ± 0,94, 12,96 ± 0,76, 14,20 ± 1,27, 12,16 ±0,47 respectively (p<0,05); leukocyte count (/mm3) were 5600, 5950, 6250, 7850 respectively (p>0.05); absolute neutrophil count (103/µL) were 3.51, 3.79, 4.72, 6.56 respectively (p<0.05); absolute lymphocyte count (103/µL) were 1.67±0.60, 1.42±0.44, 1.14±0.44, 1.14±0.59, 1.06±0.65 respectively (p<0.05); eosinophil count (103/µL) were 0.058, 0.057, 0.031, 0.023 respectively (p>0.05); and platelet count (/mm3) were 251,000 ± 61,077, 229,522 ± 59,900, 173,071 ± 57,596, 133,350 ± 44,724, respectively (p<0.05). Conclusion: The conclusion of this study is that there are differences in hemoglobin levels, absolute neutrophils, absolute lymphocytes, and platelet counts between mild, moderate, severe, and critical COVID-19 patients.